Heterogeneity of resistant mechanisms in an EGFR-TKI relapsed patient with EGFR amplification and response to nimotuzumab: A case report - Li, Yan; Xu, Ziyi; Xie, Tongji; Xing, Puyuan; Ying, Jianming; Li, Junling (Frontiers in Oncology, 2022)
EGFR mutations are the most important driver gene alterations in lung adenocarcinomas and are sensitive to EGFR-TKIs. However, resistance to EGFR-TKIs is inevitable in the majority of EGFR-mutated lung cancer patients. Numerous resistant mechanisms have been revealed to date, and more are still under investigation. Owing to the selective pressure, intratumoral heterogeneity may exist after resistance, especially in patients after multiple lines of treatments. For those patients, it is important to choose therapies focused on the trunk/major clone of the tumor in order to achieve optimal clinical benefit. Here, we will report an EGFR-mutated lung adenocarcinoma patient with heterogeneity of resistant mechanisms including EGFR amplification, large fragment deletion of RB1 and histological transformations after targeted treatments. In our case, EGFR amplification seemed to be the major clone of resistant mechanism according to the NGS results of both liquid biopsy monitoring and the tissue biopsies. In consideration of high EGFR amplification level, the patient was administered by combination treatment with EGFR-TKI plus Nimotuzumab, an anti-EGFR monoclonal antibody (mAb), and had achieved a certain degree of clinical benefit. Our case sheds light on the treatment of EGFR-mutant patients with EGFR amplification, and indicates that combination of EGFR-TKI with anti-EGFR mAb might be one of the possible treatment options based on genetic tests. Besides, decision on therapeutic approaches should focus on the major clone of the tumor and should make timely adjustments according to the dynamic changes of genetic characteristics during treatment.